Higher intakes of lysine, threonine and valine are inversely associated with non-alcoholic fatty liver disease risk: A community-based case-control study in the Chinese elderly - Xueqi Li; Wenjun Ma; Ting Yang; Chong Wang; Wei Zhang; Hui Li; Ting Zhao; Xiaofei Guo (Food Science and Human Wellness)
The associations of individual amino acid with non-alcoholic fatty liver disease (NAFLD) risk remained unclear. The present study aimed to investigate the associations between the two in the Chinese elderly. Methods: A community-based health check-up program was conducted in Qingdao, China. NAFLD was diagnosed by ultrasonography accompanied by epidemiological investigation. The dietary intakes of amino acids were investigated with 3-day, 24-h dietary records and calculated by Nutrition Calculator software. Restricted cubic spline model was used to evaluate a nonlinear relationship between amino acid intake and NAFLD risk. Results: 400 NAFLD subjects were identified, and 400 participants were randomly selected as controls and matched by gender and age (± 3 years) Dose-response analysis showed that 1 000 mg increment of aromatic amino acids (AAAs) was associated with reduced 16 % risk of NAFLD. Dietary increments of 750 mg/d threonine, 950 mg/d valine, or 1 700 mg/d lysine were associated with a 20 % reduction in the NAFLD risk (all P for linearity < 0.05). Conclusion: The present study demonstrated that the dietary increases in milk, eggs and deep-sea fish, which are rich in the amino acids, might contribute to protecting against NAFLD in the elderly.